Neural circuits provide insights into reward and aversion - Chen, Wanqi (Frontiers in Neural Circuits, 2022)
Maladaptive changes in the neural circuits associated with reward and aversion result in some common symptoms, such as drug addiction, anxiety, and depression. Historically, the study of these circuits has been hampered by technical limitations. In recent years, however, much progress has been made in understanding the neural mechanisms of reward and aversion owing to the development of technologies such as cell type-specific electrophysiology, neuronal tracing, and behavioral manipulation based on optogenetics. The aim of this paper is to summarize the latest findings on the mechanisms of the neural circuits associated with reward and aversion in a review of previous studies with a focus on the ventral tegmental area (VTA), nucleus accumbens (NAc), and basal forebrain (BF). These findings may inform efforts to prevent and treat mental illnesses associated with dysfunctions of the brain’s reward and aversion system.